An integrated kinetic and polymer science approach to investigate the textural stability of red kidney beans during post-harvest storage and subsequent cooking. (April 2022) - Wainaina, Irene; Kyomugasho, Clare; Wafula, Elizabeth; Sila, Daniel; Hendrickx, Marc
Graphical abstract: Highlights: Common beans of varying moisture were stored at temperatures at and around their Tg . Storage temperature and moisture synergistically affected cooking kinetics of beans. Textural instability of beans was mainly linked to changes in the cooking behavior. Storage above Tg strongly correlated with HTC development of beans. Abstract: Evaluation of food quality and stability during storage and processing necessitates understanding the kinetics of food functional property changes and the underlying reactions. In this study, textural stability of beans during storage and subsequent cooking was evaluated through an integrated kinetic approach. Red kidney beans stored for different periods at various conditions of temperature (25 °C − 42 °C) and moisture content (6.9% − 14.5%) relative to their glass transition temperature (Tg ) (above and around the Tg ) were studied in detail. Consequently, kinetics of softening during subsequent cooking were investigated and the dependence of these rate constants on storage time (representing the hard-to-cook (HTC) development rate) as a function of storage temperature and moisture content was evaluated. All parameters investigated, moisture content, temperature and storage time, had a significant (p < 0.05) influence on the cooking rate of beans. It was revealed that the HTC development rate of beans during storage increases with increase in temperature and moisture content, these parameters showing a synergistic effect. In addition, the rate of HTC development during storage of beans was controlled by the difference between storage temperature and Tg, showing the important role of glass transition in textural stability of beans during storage.